Dose of Inhaled Corticosteroid in Chronic Obstructive Pulmonary Disease and Risks of Osteoporosis or Fracture—A Systematic Review and Meta‐Analysis - Wang Chun Kwok; Chung Ki Tsui; Sze Him Isaac Leung; Shuk Man Ngai; David Chi Leung Lam; Mary Sau Man Ip; James Chung Man Ho (The Clinical Respiratory Journal)
ABSTRACT Background Inhaled corticosteroid (ICS) is a major pharmacotherapy for chronic obstructive pulmonary disease (COPD), which is associated with various adverse effects. Controversies exist in whether ICS use in COPD is associated with osteoporosis or fracture. Objective We performed a systematic review and meta‐analysis to assess the risks of osteoporosis or fracture at different dosing levels of ICS. High‐, medium‐ and low‐dose ICS were defined according to the Global Initiative for Asthma (GINA) step definition. Data sources Cochrane, EMBASE, Ovid, PubMed and Web of Science were systematically searched until 8 December 2023. Data extraction Osteoporosis or fracture under ICS therapy was chosen as the primary efficacy outcome. Three reviewers were involved independently in the extraction process. The risk of bias of the included studies was evaluated by using different assessment tools. Results Twenty‐one RCTs and eight observational studies were included. High‐dose ICS was associated with increased risks of osteoporosis or fracture in RCTs with RR of 1.14 (95% CI = 1.03–1.28), observational studies with healthy controls 1.14 (95% CI = 1.05–1.24) and observational studies without healthy controls 1.10 (95% CI = 1.01–1.21). High‐dose ICS was associated with increased risks in fracture in RCTs with RR of 1.12 (95% CI = 1.03–1.23), observational studies with health controls 1.15 (95% CI = 1.05–1.25) and observational studies without healthy controls 1.13 (95% CI = 1.03–1.24). Medium‐ and low‐dose ICS were not associated with osteoporosis or fracture. Conclusion High‐dose, but not medium‐ and low‐dose, ICS use in COPD is associated with risks of osteoporosis or fractures.